Retrospect on the Preparation and Application of Perovskite Materials (Journal of Solar Energy Research Updates, 2025)
In recent years, the diversity of new organic-inorganic hybrid perovskite materials has received extensive attention, for tremendous outstanding properties including large optical absorption coefficients, high carrier transport mobilities, long-range charge-carrier diffusions, low exciton binding energies, adjustable bandgaps, narrow-band bright photoluminescence as well as the compatibility of simple processing techniques. Because of these excellent properties, perovskite materials are widely used in solar cells, light-emitting devices, photodetectors, photocatalysis, etc. Here we reviewed the fundamental structure and properties of perovskite materials, and summarize the diverse preparation methods of perovskites along with the key factors in nucleation and growth control to prepare high-quality bulk crystals or films with less defects and stabilized performances against the external corrosive environments. The applications of perovskite materials accompanied with the relative bulk or interface ameliorations are discussed, and finally the prospects of such materials are expected. Overall, this review demonstrates the prevailing preparation mechanisms, challenges for high-quality perovskite materials and their vital importance in corresponding applications.